Search for Narrow High-Mass Resonances in Proton–Proton Collisions at $\sqrt{s}$ = 8 TeV Decaying to a Z and a Higgs Boson - CMS collaboration (2148 authors) (2015)
The first search for a narrow, high-mass resonance decaying into Z and Higgs (H) bosons is presented. The final state studied consists of a merged jet pair and a tau pair resulting from the decays of Z and H bosons, respectively. The analysis is based on a data sample of proton-proton collisions at a center-of-mass energy of 8 TeV, collected with the CMS experiment in 2012, and corresponding to an integrated luminosity of 19.7 inverse femtobarns. In the resonance mass range of interest, which extends from 0.8 to 2.5 TeV, the Z and H bosons are produced with large momenta, which implies that the final products of the two quarks or the two tau leptons must be detected within a small angular interval. From a combination of all possible decay modes of the tau leptons, production cross sections in a range between 0.9 and 27.8 fb are excluded at 95% confidence level, depending on the resonance mass.